Cognitiva Speciebus: Towards a Linnaean Approach to Cognition. Issue 3 (March 2021) - Millroth, Philip; Collsiöö, August; Juslin, Peter
Abstract : Research points to the limitations of approaches to decision-making, that rest on general 'Newtonian principles' derived from unitary a priori conceptions of rationality. To understand how the mind exploits environments, we instead propose a process of more open-ended discovery and systematization in the mold of Linnaeus's famous taxonomy of plants.